795 MYOCARDIAL WORK AND LEFT HEART DEFORMATION PARAMETERS ACROSS MITRAL REGURGITATION SEVERITY. (15th December 2022) - Pastore, Maria Concetta; Mandoli, Giulia Elena; Lisi, Matteo; Iuliano, Maria Alma; Paolo Niglio, Francesco; Santoro, Alfonso; Barilli, Maria; Focardi, Marta; Cavigli, Luna; D´ascenzi, Flavio; Valente, Serafina; Cameli, Matteo
Abstract: Background: Myocardial work (MW) estimation by pressure-strain loops using an implemented speckle tracking software has showed to estimate LV contractile properties overcoming the load-dependency limit of left ventricular (LV) global longitudinal strain (GLS). This has proved useful particularly in clinical setting characterized by frequent hemodynamic variations, such as heart failure and valvular heart disease. However, the variation of MW parameters across different stages of mitral regurgitation (MR) and its impact on symptoms has never been investigated. Objective: The aim of this observational study was to assess the variations of MW and deformation parameters of left heart chambers in mild, moderate and severe MR. Methods: consecutive patients with mild, moderate and severe MR were prospectively enrolled. Exclusion criteria were: chronic atrial fibrillation, valvular heart prosthesis, previous cardiac surgery.Clinical evaluation, blood sample tests, ECG and echocardiography were performed. Speckle tracking analysis completed by myocardial work were performed offline. Patients were then divided into groups first according to MR severity. Differences among the groups were analyzed by student T test (or non-parametric tests for non-normally distributed variables) and predictors of symptoms (as NYHA class ≥ 2) were explored by logistic regression analysis. Results: overall, 120 patients were enrolled (40 mild, 40 moderate, 40 severe MR). LV GLS improved according to severity, while Global PALS reduced according to MR severity. Global constructive work (GCW) and global wasted work (GWW) significantly improved in patients with moderate and severe MR, while global work efficiency (GWE) showed a trend towards reduction in patients with higher grades of MR. Global work index did not changed significantly in the three groups (Fig.1). Among strain parameters, global PALS emerged as a predictor of NYHA class (R 2 =0.2, p<0.001) These results are explained by the pathophysiology of MR, characterized by a mechanism of attempted LV compensation to volume overload with increased contractility parallel to the disease progress, although with low efficacy on increasing LV stroke volume and increased wasted work; while LA and diastolic function have an early reduction which is associated with the occurrence of symptoms. Conclusions: myocardial deformation parameters of the left heart chambers accurately reflect the pathophysiologic mechanisms of MR stages and are associated with the burden of symptoms. Fig. 1 Fig. 2